Dynamic Taxi-Sharing System Using Dual-Side Searching Algorithm - Karthika, S.; Saravanan, D. (International Journal For Research In Advanced Computer Science And Engineering, 2016)
Now-a-days taxi is an important transportation mode delivering millions of passengers to different locations in urban areas. Most of the passengers depend on taxi for travelling from one place to another. Day-by-day taxi is increasing but passengers did not get the taxi on time and wait for long time. To keep away from this issue, introducing the taxi-sharing system that accepts the passengers ride-request sent from webpage. Utilizing this application all passengers’ details can be added to the database and the administrator is given by an id and password. This id and password can be kept by the administrator. To track the client details are stored in database with id verification. The server will respond very fast for the allocation and deployment for the owner resources. And it recognizes very fast for the retrieval time also.